THE CHARACTER EDUCATION VALUES IN QUR’ANIC VERSES - Budihardjo, Budihardjo (Universitas Muhammadiyah Surakarta, 2016)
Character education is one of the main goals of education. Character education is important due to the common believe that there is the degeneration of ethic and moral of the learners, and also due the rise of juvenile delinquency. Then, character education comes to recover it. Character education can be integrated in various aspects, such as in study al-Qur’ān. The integration between character education and the interpretation of al-Qur’an will make new insight of character education. Moreover, it will be strengthened by the words of Allah. This particular research is intended to reveal whether studies about character education in al-Qur’an will provide a particular kind of character education based on Qur’anic verses, and whether there is any relevance between character education as presented in Qur’anic verses with those presented in curriculum 2013?. To answer these questions, the researcher used descriptive comparative approach, library research as the kind of research, and the use of documentary for collecting the data. This study shows that there are some character education as presented in Qur’anic verses and that there is a relevance between character education values in curriculum 2013 and character education in Qur’anic verses. From the relevance, it is concluded that the character education as presented in Qur’anic verses suggest similar goals as the character education value in curriculum 2013. Pendidikan karakter merupakan salah satu tujuan utama dari pendidikan itu sendiri. Pendidikan karakter sangat penting diajarkan kepada peserta didik lantaran adanya kepercayaan di kalangan masyarakat bahwa dewasa ini telah terjadi degradasi moral dan kenakalan pada peserta didik. Sehingga hadirnya pendidikan karakter dirasa sangat penting untuk memulihkan problem di atas. Apalagi, jika pendidikan karakter itu diintegrasikan dengan nilai-nilai pendidikan yang ada dalam studi al-Qur'an. Untuk itu penelitian ini dimaksudkan untuk mengungkapkan bagaimana studi tentang pendidikan karakter jika dikaitkan dalam perspektif al-Qur'an?, dan apakah ada relevansi antara pendidikan karakter seperti yang disajikan dalam ayat-ayat al-Qur’an dengan yang disajikan dalam kurikulum 2013?. Untuk menjawab pertanyaan ini, peneliti menggunakan pendekatan komparatif deskriptif, penelitian kepustakaan sebagai jenis penelitian, dan penggunaan dokumenter untuk mengumpulkan data. Studi ini menunjukkan bahwa ada beberapa pendidikan karakter seperti yang disajikan dalam ayat-ayat al-Quran, dan ditemukan ada relevansi antara nilai pendidikan karakter dalam kurikulum 2013 dan pendidikan karakter dalam ayat-ayat al-Qur’an. Begitu juga ditemukan bahwa nilai-nilai pendidikan karakter sebagaimana yang terdapat dalam ayat-ayat al-Qur’an, ternyata selaras dengan nilai-nilai pendidikan karakter yang ada dalam kurikulum 2013.